Fidelity in Translating Religious Practice: Illustrations from Filipino Christanity - Francisco, Jose Mario C., SJ (Archīum Ateneo, 2024)
What fidelity consists in has always been a central concern in translation studies and practice. This essay first discusses its shifting meaning in relation to the various turns in contemporary translation theory, and their application to the translation of religious practice. It then examines the translation of late medieval post-Reformation Spanish Catholicism into Filipino Christianity through an analysis of its texts and performances. It concludes by revisiting the meaning of fidelity and relates it to root-metaphors for translation in some Philippine languages. Fidelity appears not as the transfer of an unchanging meaning but as the recognition of self within the fluid interaction of languages and contexts.